2017
DOI: 10.3389/fpls.2017.00454
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Starch Synthase III-1 in Amylopectin Metabolism of Banana Fruit: Characterization, Expression, Enzyme Activity, and Functional Analyses

Abstract: Soluble starch synthase (SS) is one of the key enzymes involved in amylopectin biosynthesis in plants. However, no information is currently available about this gene family in the important fruit crop banana. Herein, we characterized the function of MaSSIII-1 in amylopectin metabolism of banana fruit and described the putative role of the other MaSS family members. Firstly, starch granules, starch and amylopectin content were found to increase during banana fruit development, but decline during storage. The SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Further Western blot analysis suggested that the protein was gradually increased during banana fruit development, but drastically reduced during storage. Lastly, over expression of MaSSIII-1 in tomato plants distinctly changed the morphology of starch 67 .Chemical constituents, radical scavenging activity and enzyme inhibitory capacity of fruits from Cotoneaster pannosus Franch. Cotoneaster pannosus (Rosaceae) is a semievergreen shrub, producing globose dark red pomes, native to China and widely used as an ornamental plant all over the world.…”
Section: Introductionmentioning
confidence: 97%
“…Further Western blot analysis suggested that the protein was gradually increased during banana fruit development, but drastically reduced during storage. Lastly, over expression of MaSSIII-1 in tomato plants distinctly changed the morphology of starch 67 .Chemical constituents, radical scavenging activity and enzyme inhibitory capacity of fruits from Cotoneaster pannosus Franch. Cotoneaster pannosus (Rosaceae) is a semievergreen shrub, producing globose dark red pomes, native to China and widely used as an ornamental plant all over the world.…”
Section: Introductionmentioning
confidence: 97%
“…During the development of a banana, starch and amylopectin accumulate gradually and starch’s synthase (SS; EC2.4.1.21) activity increases until the late stage, remaining constant during starch breakdown (climacteric). However, it almost vanishes during storage and is accompanied by amylopectin and starch granule degradation [ 6 ]. Only β-amylase (EC3.3.1.2) activity increased before onset of the respiration peak and along with starch decrease.…”
Section: Introductionmentioning
confidence: 99%
“…The expression level of SPS increased distinctly but showed a very low activity at the onset of the climacteric stage and then steadily increased during the post climacteric stages. Moreover, little content of Fructose 2,6-bisphosphate (Fru(1,6)P2; EC3.1.3.46) was found in unripe fruit but increased markedly with an increased respiration rate [ 6 ]. The expression of uridine diphosphoryl (UDP)-glucose pyrophosphorylase (UGPase, EC2.7.7.9) in banana pulp was higher than that in peel and consistent with starch degradation and sucrose synthesis in pulp.…”
Section: Introductionmentioning
confidence: 99%
“…Starch is the most abundant storage polysaccharide in plants. As an important carbohydrate and energy source in the human diet and nutrition, starch is massively produced in cassava ( Manihot esculenta ) roots [ 1 ], potato ( Solanum tuberosum ) tubers [ 2 ], cereal seeds [ 3 ], and a number of fresh fruits such as banana ( Musa acuminata ) [ 4 , 5 , 6 , 7 , 8 ]. The biosynthesis of starch in plants is a complex process involving a variety of enzymes, such as ADP-glucose pyrophosphorylase (AGPase), granule-bound starch synthase (GBSS), soluble starch synthase (SS), starch branching enzyme (SBE), and debranching enzyme (DBE) [ 2 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…With starch content reaching 74–88% of its dry weight in unripe fruit, M. acuminata is not only the most popular starch-rich fresh fruit in the world, but also an important staple food in some African and Latin American countries [ 6 , 7 , 8 , 33 , 34 ]. Starch biosynthesis is of crucial importance since starch content determines fruit yield, quality, and economic value of banana.…”
Section: Introductionmentioning
confidence: 99%